ՀՀ տնտեսության համար «Օտարերկրյա ուղղակի ներդրումներ - տնտեսական աճ» կապի վերլուծությունը - Խառատյան, Ալվարդ; Պետրոսյան, Անուշիկ; Եղոյան, Կարեն (ԱԵԳՄՄ հրատ.)
The growth of foreign direct investment (FDI) as a component of GDP certainly contributes to economic growth. However, one should not forget that the relationship "economic growth - FDI" is "bi-directional", that is, in addition to the fact that FDI stimulates growth, it is also affected by economic growth. If there are many scientific and practical studies on the first, "traditional" direction of this "two-way" relationship, its other side - the impact of economic growth on FDI, has not been sufficiently studied. The goal of this article is to evaluate the impact of the growth of RA economy sectors on FDI using regression models. In the given article, the RA economy was regarded as an aggregate of the following sectors: industry, agriculture, construction, services and trade. Multi-factor regression models were built in order to identify and evaluate the connections between FDI and economy sectors in RA. An economic analysis of the results obtained by the models was also performed, and the impact on FDI was estimated for each of the considered factors. Particularly, the econometric analysis shows that, other conditions being equal: • 1% increase in the growth rate of industrial output leads to a 2.6% decrease in the volume of FDI. • 1% growth of the service sector contributes to the 5.5% growth of the volume of FDI. • 1% increase in agriculture leads to a 4.2% increase in the volume of FDI. • Increase in the trade sector leads to the increase of FDI volume, whereas the increase in the construction leads to the decrease of it. Рост прямых иностранных инвестиций (ПИИ) как компоненты ВВП, безусловно, способствует экономическому росту. Однако не следует забывать, что связь «экономический рост – ПИИ» является «двусторонней», то есть, помимо того, что ПИИ стимулируют рост, в свою очередь, они подлежат влиянию экономического роста. Если по первому, «традиционному» направлению этой «двусторонней» связи имеется множество научных и практических исследований, то другая ее сторона — влияние экономического роста на ПИИ — недостаточно изучена. Целью данной статьи является оценка влияния роста секторов экономики РА на ПИИ с использованием регрессионных моделей. В статье экономика РА рассматривается как совокупность следующих отраслей: промышленность, сельское хозяйство, строительство, услуги и торговля. С целью выявления и оценки связей между ПИИ и секторами экономики РА были построены многофакторные регрессионные модели. Также был проведен экономический анализ результатов этих моделей, оценено влияние на ПИИ каждого из рассмотренных факторов. В частности, эконометрический анализ показывает, что при прочих равных условиях: • увеличение темпов роста промышленного производства на 1% приводит к снижению объема ПИИ на 2.6%. • рост сектора услуг на 1% способствует росту объема ПИИ на 5.5%. • рост сельского хозяйства на 1% приводит к увеличению объема ПИИ на 4.2%. • увеличение торгового сектора приводит к увеличению, а увеличение сектора строительства к снижению объема ПИИ.
Keywords: Տնտեսագիտություն